Searches for new physics in top decays at the LHC - Onofre, A. (2012)
The search for new physics in top quark decays at the LHC is reviewed in this paper. Results from ATLAS [1] and CMS [2] experiments on top quark decays within the Standard Model are presented together with the measurements of the W boson polarizations and the study of the structure of the Wtb vertex. As a natural step forward, the experimental status on measurements sensitive to top quark couplings to gauge bosons (γ, Z, W and H) is reviewed as well as possible top quark decays Beyond the Standard Model (MSSM and FCNC).